Changes in lower extremity blood flow during advancing phases of pregnancy and the effects of special footwear - Gimunová, Marta; Zvonař, Martin; Kolářová, Kateřina; Janík, Zdeněk; Mikeska, Ondřej; Musil, Radek; Ventruba, Pavel; Šagat, Peter (Jornal vascular brasileiro, 2017)
Background: During pregnancy, a number of changes affecting venous blood flow occur in the circulatory system, such as reduced vein wall tension or increased exposure to collagen fibers. These factors may cause blood stagnation, swelling of the legs, or endothelial damage and consequently lead to development of venous disease. Objectives: The aim of this study is to evaluate the effect of special footwear designed to improve blood circulation in the feet on venous blood flow changes observed during advancing phases of pregnancy. Methods: Thirty healthy pregnant women participated in this study at 25, 30, and 35 weeks of gestation. Participants were allocated at random to an experimental group (n = 15) which was provided with the special footwear, or a control group (n = 15). At each data collection session, Doppler measurements of peak systolic blood flow velocity and cross-sectional area of the right popliteal vein were performed using a MySonoU6 ultrasound machine with a linear transducer (Samsung Medison). The differences were compared using Cohen's d test to calculate effect size. Results: With advancing phases of pregnancy, peak systolic velocity in the popliteal vein decreased significantly in the control group, whereas it increased significantly in the experimental group. No significant change in cross-sectional area was observed in any of the groups. Conclusions: Findings in the experimental group demonstrated that wearing the footwear tested may prevent venous blood velocity from reducing during advanced phases of pregnancy. Nevertheless, there is a need for further investigation of the beneficial effect on venous flow of the footwear tested and its application.